Cerebellar hemorrhage after spinal surgery: case report and review of the literature - (:unkn) unknown (SPRINGER, 2006)
Recent reports indicate that cerebellar hemorrhage after spinal surgery is infrequent, but it is an important and preventable problem. This type of bleeding is thought to occur secondary to venous infarction, but the exact pathogenetic mechanisms are unknown. This report details the case of a 48-year-old woman who developed remote cerebellar hemorrhage after spinal surgery. The patient presented with a herniated lumbar disc, spinal stenosis, and spondylolisthesis, and underwent multiple-level laminectomy, discectomy, and transpedicular fixation. The dura mater was opened accidentally during the operation. There were no neurologic deficits in the early postoperative period; however, 12 h postsurgery the patient complained of headache. This became more severe, and developed progressive dysarthria and vomiting as well. Computed tomography demonstrated small sites of remote cerebellar hemorrhage in both cerebellar hemispheres. The patient was treated medically, and was discharged in good condition. At 6 months after surgery, she was neurologically normal. The case is discussed in relation to the ten previous cases of remote cerebellar hemorrhage documented in the literature. The only possible etiological factors identified in the reported case were opening of the dura and large-volume cerebrospinal fluid loss.
Keywords: cerebellar hemorrhage; dural injury; hemorrhagic infarction; spinal surgery; POSTOPERATIVE HEMORRHAGE; CRANIOTOMY; COMPLICATION; INFARCTION